Resilience in the Technological Era in Support of the Sustainability Agenda - Moh. Hafid Effendy; Saiful Hadi; Mochammad Arifin Alatas (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Digitalization and globalization are transforming local cultures into digital spaces while challenging the sustainability of Madurese cultural identity. This study aims to analyze the forms and mechanisms of cultural resilience among the Madurese community in responding to these changes. A qualitative approach with a multiple case study design was employed through in-depth interviews with 24 purposively selected informants. Data were analyzed using the interactive model of Miles et al., involving data condensation, data display, and conclusion drawing, with validity ensured through triangulation and member checking. The findings reveal five key dimensions of cultural resilience: technological adaptation, transformation of cultural expressions into digital spaces, strengthening of a culture-based economy, cultural filtering mechanisms, and global expansion of cultural identity. Digitalization functions both as a medium for cultural preservation and as an economic opportunity, guided by religious and customary values. Integrating technology with local culture reinforces cultural sustainability and highlights the importance of community-based empowerment policies.